Muslim Society Needs For Learning The Vocabulary Meaning Of Surah Al-Fatihah Through Mobile Phone Applications/ احتياجات المجتمع المسلم إلى تعلُّم معاني مفردات سورة الفاتحة عبرالتطبيقات الهاتفية - Alosman, Abdulrahman; Hamawiya, Adham (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Previous studies reveal the need for the Muslim community to know the exact meaning of the vocabulary of Surah Al-Fatihah and understand it in depth. This research aims to identify these needs among the Muslim community based on their perceptions of using them, especially using telephone applications. The research used an inductive and analytical approach to explore the needs of the Muslim community regarding telephone application design elements to study the meaning of the vocabulary of Surah Al-Fatihah. The tool used was a questionnaire distributed to respondents from the research sample. The research results show that respondents have a high level of acceptance of learning the meaning of Surah Al-Fatihah vocabulary through mobile applications, and they also prefer various valuable functions and presentation methods in the application, in addition to the availability of modern educational facilities—content to suit different learner levels. In addition, it becomes clear that the results of this research can be used as a basis for designing telephone applications to study the meaning of the vocabulary of Surah Al-Fatihah.